Shape manipulation of ion irradiated Ag nanoparticles embedded in lithium niobate. (23rd February 2016) - Wolf, Steffen; Rensberg, Jura; Johannes, Andreas; Thomae, Rainer; Smit, Frederick; Neveling, Retief; Moodley, Mathew; Bierschenk, Thomas; Rodriguez, Matias; Afra, Boshra; Hasan, Shakeeb Bin; Rockstuhl, Carsten; et al.
Abstract: Spherical silver nanoparticles were prepared by means of ion beam synthesis in lithium niobate. The embedded nanoparticles were then irradiated with energetic 84 Kr and 197 Au ions, resulting in different electronic energy losses between 8.1 and 27.5 keV nm −1 in the top layer of the samples. Due to the high electronic energy losses of the irradiating ions, molten ion tracks are formed inside the lithium niobate in which the elongated Ag nanoparticles are formed. This process is strongly dependent on the initial particle size and leads to a broad aspect ratio distribution. Extinction spectra of the samples feature the extinction maximum with shoulders on either side. While the maximum is caused by numerous remaining spherical nanoparticles, the shoulders can be attributed to elongated particles. The latter could be verified by COMSOL simulations. The extinction spectra are thus a superposition of the spectra of all individual particles.